Economically driven requirements for a hybrid-electric 19-passenger commuter aircraft. Issue 1 (January 2021) - Schuh, G; Spangenberg, M; Zhang, Q
Abstract: The appeal of reduced travel and transport times and electrification of aircraft drive the development of new aircraft for short distances. The goal of the CleanSky2 project ELICA (ELectric Innovative Commuter Aircraft) is to provide a preliminary design of a hybrid-electric 19-passenger commuter aircraft, whereby the passenger limit is defined by certification. This paper describes the initial set of Top Level Aircraft Requirements (TLARs) based on both a benchmark with existing 19-passenger commuter aircraft and the analysis of requirements derived from potential future markets Regional Air Mobility (RAM) and thin-haul air cargo services. Both of these are introduced briefly. A literature-based framework for TLARs and an analysis of existing airfield infrastructure in Europe and the US together with population data in the direct surroundings of such airfields are investigated. Additionally, insights on cabin design are discussed and important features such as noise emissions and operational cost of such aircraft are highlighted.